THE SIGNIFIER AND SIGNIFIED OF FASHION POWER IN THE DEVIL WEARS PRADA: A SAUSSUREAN SEMIOTIC ANALYSIS - Syahidah, Fatimah; Nur Sakinah, Myrna (Fakultas Ilmu Budaya, Universitas Padjadjaran, 2026)
This research examined the semiotic construction of fashion power in the film The Devil Wears Prada by applying Saussure’s concepts of the signifier and the signified. The topic was important because fashion in cinema often influences public perceptions of professionalism, social legitimacy, and identity, yet its meaning-making process has rarely been explained in structural detail. The purpose of the study was to examine how fashion communicates power and social belonging in the film’s workplace setting. The research employed a qualitative descriptive method, in which twenty scenes were analyzed by documenting visual elements of costume, footwear, accessories, and bodily presentation, and by interpreting their symbolic meanings within a semiotic framework. The findings showed that fashion consistently acted as a signifier of authority, social acceptance, and identity negotiation, and even subtle auditory cues such as the sound of heels contributed to hierarchical meaning. The study concluded that fashion does not simply decorate the narrative but functions as the core mechanism through which power relations and character transformation are communicated. These results suggest that fashion in visual media shapes the audience’s understanding of professional success and that mastery of visual codes is represented as a requirement for social legitimacy in the workplace.